Patients' understanding of tetanus immunisation. Issue 4 (July 1996) - Davies, F; Luke, L C; Burdett-Smith, P
Abstract : OBJECTIVE: To investigate patients' understanding of the use of adsorbed tetanus toxoid (ATT) in an accident and emergency (A&E) unit. METHODS: 500 patients attending the minor injuries unit of the Royal Liverpool University Hospital in one calendar month completed a questionnaire under the supervision of the triage nurse. Analysis of results was at the 95% confidence level. Occupation was used as a guide to social class. RESULTS: Analysis of 296 male and 204 female respondents revealed that 50.4% thought that ATT is an antibiotic and 81% thought it protected against wound infection; 35.6% thought that concurrent antibiotic treatment would be rendered unnecessary. There was a significant gradient in accuracy of response from social classes I to V for each question. CONCLUSIONS: While few patients refuse the offer of ATT immunisation, true understanding of its purpose and limitations is lacking. This may reduce awareness of potential wound infection and possibly decrease compliance with concurrent antibiotic prescription. A&E and primary care staff should acknowledge the prevalence of these misunderstandings and assist in patient education.